Economic theory and (ontological) reductionism: some pitfalls in the road of the microfoundations project - Neris Jr., Celso Pereira; Fucidji, José Ricardo (Brazilian Keynesian Review, 2021)
This paper aims to survey the literature on the theoretical enterprise of providing the microfoundations of macroeconomics. To do so, it evaluates that project from the viewpoint of economic methodology, mostly of critical realism. Its novelty lies in analysing the reductionism inbuilt in the project and its unsuitability both to its own terms and to the purpose of illuminating socioeconomic reality. We also stress that, in addition to a project of science (the sound or rigorous way of doing ‘scientific’ economics), it includes an implicit ontology of market sociability that establishes links between microfoundations and the neoliberal ideology. Some attempts at overcoming the reductionist individualism of microfoundations are also evaluated, such as complexity theory and old institutionalism, pointing out its potential and shortcomings. In order to deal with a complex, hierarchically multi-level structured and open reality, economic theory should not adopt explanations that give precedence to a single level. It should instead prefer approaches in which micro and macro levels are mutually conditioned and relatively autonomous.